Neoadjuvant Chemotherapy Followed by Radiofrequency Ablation Prolongs Survival for Ablatable Colorectal Liver Metastasis: A Propensity Score Matching Comparative Study - Chen, Yizhen; Xu, Youyao; Xu, Linwei; Han, Fang; Huang, Yurun; Jiang, Hang; Wu, Jia; Zhang, Yuhua (Frontiers in Oncology, 2021)
Background: Typically, Colorectal liver metastasis (CRLM) is not a candidate for hepatectomy. Radiofrequency ablation (RFA) plays a critical role in unresectable CRLM patients. Nevertheless, high local tumor progression (LTP) and distant metastasis limit the development and further adoption use of RFA. Neoadjuvant chemotherapy (NAC) has been widely used in resectable CRLM and is recommended by the guidelines. There are no studies on whether NAC can improve the prognosis in ablatable CRLM patients. The present study aimed to determine the feasibility and effectiveness of RFA plus NAC. Methods: This retrospective cohort included CRLM patients from Zhejiang Cancer Hospital records, who received RFA from January 2009 to June 2020 and were divided into two groups according to the presence or absence of NAC. The Kaplan–Meier method was used to evaluate the 3-year local tumor progression-free survival (LTPFS), progression-free survival (PFS), and overall survival (OS) of the two groups. Use propensity score matching to reduce bias when assessing the survival. Multivariate Cox proportional hazards regression analysis was used to study the independent factors affecting LTPFS, PFS, and OS. Results: A total of 149 CRLM patients (88 in the RFA alone group and 61 in the plus NAC group) fulfilled the inclusion criteria. Post-RFA complications were 3.4% in the RFA alone group and 16.4% in the plus NAC group. The 3-year LTPFS, PFS, and OS of the RFA only group was 67.0%, 25.0%, and 51.9%, respectively. The 3-year LTPF, PFS, and OS of the plus NAC group was 86.9%, 50.8%, and 77.0%, respectively. In the 29 pairs of propensity score matching cohorts, the median LTPFS, PFS and OS in the plus NAC group were longer than those in the RFA group (p<0.05). NAC was an independent protective factor for LTPFS, PFS, and OS (p<0.05). Conclusions: For ablatable CRLM patients, RFA plus NAC obtained a better prognosis than RFA alone. Based on the current results, the application of NAC before RFA may become the standard treatment.